Neuropathic Pain Relief after Surgical Neurolysis in Patients with Traumatic Brachial Plexus Injuries: A Preliminary Report - Armando Armas-Salazar; Noe Téllez-León; Ana Isabel García-Jerónimo; Francisco Alberto Villegas-López; José Luis Navarro-Olvera; José Damián Carrillo-Ruiz (Pain Research and Management)
Objective. To evaluate the usefulness of surgical neurolysis for neuropathic pain relief in patients with posttraumatic brachial plexus injury (BPI). Methods. A prospective, longitudinal, nonrandomized, self-controlled before and after study was performed to evaluate the pain changes according to their intensity using the Visual Analogue Scale (VAS), and the sensory recovery after surgery using the British Medical Research Council (BMRC) scale for sensory recovery. To establish significant changes, a paired T-test was performed, and in order to determine the magnitude of these changes, an effect size was measured. α = 0.05. Results. Ten patients were included with an average follow-up of 61.9 ± 53.62 months. The main mechanism of injury was vehicular trauma (70%). A significant decrease in pain after the surgical intervention was observed resulting from an average preoperative state according to VAS of 8.4 ± 1.58, to a postoperative state of 3.4 ± 3.27 (59.52%, p = 0.005, Δ = 1.572), added to a mean sensory improvement (25%) from 2.8 ± 1.62 to 3.5 ± 0.97 after surgery according to BMRC, without statistically significant changes (p=0.062), showing a moderate effect size (Δ = 0.413). Almost all patients showed improvement in the continuous and paroxysmal pattern of pain. No postoperative complications were observed. Discussion. These results suggest that in cases of BPI that originates from a compressive syndrome secondary to the posttraumatic fibrosis that surrounds the nerve structures causing strangulation and inducing hypernociception, the use of surgical neurolysis is an appropriate alternative for patients with medically refractory neuropathic pain.